A misunderstood new gecko of the genus Hemidactylus from Socotra Island, Yemen (Reptilia: Squamata: Gekkonidae) - Sindaco, Roberto; Ziliani, Ugo; Razzetti, Edoardo; Carugati, Caterina; Grieco, Cristina; Pupin, Fabio; Al-Aseily, Badr Awadh; Pella, Francesca; Fasola, Mauro (Acta Herpetologica, 2009)
A new endemic gecko of the genus Hemidactylus is described from Socotra Island (Yemen). It is a rupicolous species characterized by: medium-large size (SVL up to 60 mm), back with large trihedral, raised, strongly keeled tubercles intermixed with small granular scales, males with 6-10 preanal pores arranged in two short rows separated by 2-3 scales. In East Africa, Arabia, the Middle East and India the only other tuberculated Hemidactylus with preanal pores arranged on two separate rows is the Somali H. granchii Lanza, 1978, which differs for the comparatively deeper and shorter head, the nostril separated from the first upper labial, less preanal pores, less upper and lower labials, more tubercles at midbody and more lamellae under the inner toe.